Reduced Amputation Rate by Circular TNP Application on Split-Skin Grafts After Deep Dermal Foot Scalds in Insulin-Dependent Diabetic Patients. Issue 5 (September 2015) - Kisch, Tobias; Liodaki, Maria E.; Mauss, Karl L.; Kalousis, Konstantinos; Wenzel, Eike T.; Mailaender, Peter; Stang, Felix H.
<x xml:space="preserve">Abstract</x> The incidence of insulin-dependent diabetes mellitus (IDDM) is expected to increase significantly. Due to peripheral neuropathy and angiopathy in IDDM patients, feet scalding results in deep burn injuries. Regularly amputations are needed with tremendous consequences. In relatively healthy patients, split-skin graft (SSG) take is better when topical negative pressure (TNP) is applied. We compared the outcome of circular TNP dressing with that of antiseptic dressing on freshly laid SSG after tangential excision in IDDM patients with deep dermal foot scalds. Seventy patients admitted to a burn center with isolated foot burns were identified (2008–2013). Ten of them suffered from IDDM and presented with a deep dermal foot scald. After tangential excision and split-skin grafting, five of them were treated with TNP. The others received an antiseptic dressing regime. Differences were analyzed using either Chi-square or Student's t-test. Group comparison regarding age, gender, body mass index, HbA1c on arrival, glucose in serum, IDDM disease duration, and TBSA revealed no significant differences. But percentage of graft take was at a significantly higher rate in the TNP group (90.2 ± 4.017 vs 39 ± 15.362) and fewer operations had to be performed compared to the control group (2.0 ± 0.447 vs 4.6 ± 0.927). Due to reduced occurrence of necrosis, the number of amputations required was significantly lower in the TNP group. TNP application on freshly laid SSG following tangential excision in IDDM patients after deep dermal foot scalds minimized amputation rates and therefore is of great benefit for such patients.